Impact of the Digital Skills on Employability: Cross-Sectional Analysis - Biljana Đorđević; Sandra Milanović Zbiljić; Marija Radosavljević (Economies)
Digital skills are increasingly vital for enhancing employability, as they equip individuals to meet the evolving demands of the modern workforce. Therefore, this paper examines the impact of digital skills on employability, focusing on the influence of both basic and above-basic levels of information and data literacy, communication and collaboration, problem-solving, digital content creation, and safety skills, considered key components of digital competence. The research employs regression analysis using secondary data extracted from the Eurostat database. Based on data from 32 European countries, the findings indicate that three proxies for digital skills, communication and collaboration, digital content creation, and safety, significantly and positively influence employability. The contribution of this paper to the existing literature on digital skills and employability is twofold. First, by evaluating the influence of five categories of digital skills across different proficiency levels on employment rates, the study sheds light on which specific digital skills have the most substantial impact on employability in today’s labor market. Second, the findings provide a foundation for formulating recommendations aimed at enhancing the digital capabilities of the labor force.